Dawah as the prophetic mission - Farooqui, Jamil (Radiance Views Weekly, 2010)
Dawah is an invitation to someone to participate in some event or to do something. Islamic Dawah is the call to the Truth, to the way of God, the straight path, as well as to the virtuous, dignified and contended life. It invites humanity to comprehend and invoke the ‘Absolute Reality’, a living force behind all realities that derive their strength and vitality from it. It is the call to come closer to Allah the Exalted, the Lord and Master of the universe, the Most Glorious, Powerful, of Whom it is said “there is none like Him” (Qur’ān, 112:4).